Ural eye and medical study: description of study design and methodology - Bikbov, Mukharram; Jonas, Jost B. (Ophthalmic epidemiology, 2018)
Purpose: Since there is a scarcity on population-based health information available for Russia, we conducted this project to assess the prevalence of major ocular and systemic disorders and their associated risk factors.Methods: A population-based cross-sectional study (Ural Eye and Medical Study (UEMS)) was performed in Bashkortostan 1300 km east of Moscow. The sampling frame consisted of all inhabitants aged over 40 years and living in an urban study area in the capital city Ufa and a rural region at 65 km outside of Ufa. The target sample size was 2500 individuals for the urban region and 2500 persons for the rural region. The study participants underwent a detailed interview, a detailed ophthalmologic examination including biometry and optical coherence tomography, and clinical examination including assessment of electrocardiography, hearing test, blood sampling, spirometry, and hand grip dynamometry.Results: After a first study period, the study population included 4254 individuals with a mean age of 60.3 ± 11.1 years (range: 40-94 years), mean body weight of 74.8 ± 14.4 kg (range: 31-170 kg), body height of 163.6 ± 8.9 cm (range: 112-196), body mass index of 28.0 ± 5.1 kg/m2 (range: 13.96-60.96 kg/m2), mean systolic blood pressure of 133.7 ± 21.0 mmHg (range: 84-232 mmHg), and mean diastolic blood pressure of 81.2 ± 10.6 mmHg (range: 40-134 mmHg). Mean refractive error was −0.21 ± 1.94 D and mean intraocular pressure was 13.6 ± 3.9 mmHg.Conclusions: The UEMS provides population-based normative data for a Russian region on the quantitative traits such as axial length, quality of life and lifestyle including smoking and alcohol consumption, and prevalence and risk factors of ocular and systemic diseases such as diabetes mellitus, arterial hypertension, chronic obstructive pulmonary disease, and depression.